Flow past a self-oscillating airfoil with two degrees of freedom: measurements and simulations - Šidlof Petr; Štěpán Martin; Vlček Václav; Řidký Václav; Šimurda David; Horáček Jaromír (EPJ Web of Conferences, 2014)
The paper focuses on investigation of the unsteady subsonic airflow past an elastically supported airfoil for subcritical flow velocities and during the onset of the flutter instability. A physical model of the NACA0015 airfoil has been designed and manufactured, allowing motion with two degrees of freedom: pitching (rotation about the elastic axis) and plunging (vertical motion). The structural mass and stiffness matrix can be tuned to certain extent, so that the natural frequencies of the two modes approach as needed. The model was placed in the measuring section of the wind tunnel in the aerodynamic laboratory of the Institute of Thermomechanics in Nový Knín, and subjected to low Mach number airflow up to the flow velocities when self-oscillation reach amplitudes dangerous for the structural integrity of the model. The motion of the airfoil was registered by a high-speed camera, with synchronous measurement of the mechanic vibration and discrete pressure sensors on the surface of the airfoil. The results of the measurements are presented together with numerical simulation results, based on a finite volume CFD model of airflow past a vibrating airfoil.